tudy of failures in a distributed environment: New coordinated and communication induced checkpointing protocols - ABDELHAFIDI , Zohra; YAGOUBI Mohamed Bachir (Université de Laghouat , Bibliothèque centrale, 2017)
Distributed systems are prone to failures, so it is important that these systems can find a consistent global state from which the execution can resume: this is the problem in which we are interested A comprehensive study will be conducted on existing algorithms such as checkpointing protocols to solve the failure problem. that will enable us subsequently to develop new techniques and introduce new concepts and to possibly propose a new solution.